Land-use Change; Achilles heel to Overcoming the Environmental Crisis, Process and Impacts - Mosayeb Heshmati; Mohamad Gheitouri (جغرافیا و پایداری محیط, 2018)
Natural resources including forests, rangelands, rivers, sea shores, water fall, some mountainous landscapes such as caves, debris and alluvium fan are considered as unique heritages due to their contributions on environmental services and sustainability. However, these valuable resources are degraded mainly through anthropogenic land-use. Overcoming climate change and land resources degradation depends on controlling land-use change and saving our natural heritages, so that it is Achilles heel for overcoming environmental crisis. There are many factors contributing to land-use change mainly including climate change, land tenure and ownership, urbanization, official and legal shortcoming. Based on literature review and field verification, the climate change is more serious in semiarid areas due to lower precipitation and higher hydrological lost. Despite the drastic increase of water demand during drought both runoff losses and deforestation processes severely accelerate the land-use change. Decline the forest and rangeland area as well as soil nutrient and organic carbon depletion are the important on-site impacts of land-use change. Furthermore, the areas of fair rangeland are being shifted to poor condition due to both conversion to rain-fed lands and overgrazing. Climate change is the main aspects of land-use alteration due to negative change in soil quality, particularly the critical extrinsic characteristics including SOC, soil nutrients, soil aggregates and bulk density. If current land degradation and land-use change continue, other impacts in terms of water deficit, desertification and migration can be spread throughout the semiarid region of Iran. Absolutely, overcoming these challenges depends upon saving our heritages including natural resources, unique landscapes, and an attempt to do proper agricultural activities. Extended Abstract 1-Introduction Natural resources including forests, rangelands, rivers, sea shores, water fall, some mountainous landscapes such as save, debris and alluvium fan are considered as unique heritages due to their contributions on environmental services and sustainability. Furthermore, they are main adapting sources for combating climate change impacts in terms of erosion, flash floods, drought, dust and desertification. However, these valuable resources are degraded mainly through anthropogenic land-use change in terms of deforestation, converting to steep rain-fed lands, overgrazing and improper tillage practice. Declining of forest and rangeland areas as well as soil erosion are more severe in mountainous and hilly lands of upper catchments of dry-lands. This occurs because of population pressure, government policy, market demand and climate change as well as urbanization in the lowland areas, resulting in expansion of cultivation in the highlands. Most parts of natural resources in the mountainous and hilly area of Iran located in geological marly formations comprising fine grained materials such as clay and silt contents. Thus, due to accelerated land-use change and improper agricultural activities, both on-sit and off-site consequences in terms of siltation, dust blown, water scarcity, pests, flood, landslide incidence and soil carbon emission are spread throughout semiarid region of Iran. By and large, overcoming climate change and land resources degradation depends upon controlling of land-use change and saving our natural heritages, so that there is Achilles heel for overcoming environmental crisis. 2-Materials and Methods The review paper focused on land-use change and its impacts based on several research works in relation to land-use change in the semiarid regions, their study in other countries as well as reviewing recent relevant research reports worldwide. The conclusion and some main approaches solution were pointed based on climate change conditions. 3-Results and Discussion There are many factors contributing to land-use change mainly including climate change, land tenure and ownership, urbanization, official and legal shortcoming. Based on literature review and field verification during recent decade, the climate change is more serious in semiarid due to lower precipitation and higher hydrological lost such as runoff and evaporation causing forest mortality and drying of rivers borders, grasslands and spring territory promoting tillage practice and converting to arable lands. In addition, drought stress promotes outbursts pests and outbreak diseases in the forest, especially Zagros Forest. Despite the drastic increase of water demand during drought period, both runoff losses and evaporation agents severely accelerate the land-use change. Although rangelands and forests in Iran have been nationalized, the protection and rehabilitation programs could not be done successfully, because the current laws and administrative office were unable to confine the current level of land-use alteration, even though cause conflict of interest between land owners and environmentalists on the extraction of natural resources. The rapid expansion of urban areas due to rise in population and economic growth is increasing and additional demand on natural resources thereby causes land-use changes especially in megacities. It is estimated that about 4000 ha suitable irrigation lands with fertility soils are being converted to seven megacities annually in Iran. Consequently the agricultural lands have been drastically reduced from 0.6 (1945) to 0.16 (2004) ha per capita. There are several aspects of land-use change which can be divided into on-site and off-site effects. Declining of forest and rangeland area, soil organic carbon (SOC) and soil nutrients depletion are the important on-site impacts of land-use change. SOC decline resulted in both on-site and off-site impacts because of its multi-functions including primary source of plant nutrients, water holding, soil infiltration, soil aggregation and atmosphere carbon sink. Due to high clay and silt content and dominant smectite mineralogy in the Zagros regions, extreme on-sites consequence such as gully erosion and landslide occurrence with off-site impacts such as flood and even dust phenomena are aggressively being spread. In these regions, annually 130 thousand ha oak forest are degraded. Furthermore, the areas of fair rangeland are being shifted to poor rangeland and steep rain-fed lands due to both conversion to rain-fed lands and overgrazing. Climate change is the main aspects of land-use alteration due to negative change in soil quality, particularly the critical extrinsic characteristics including SOC, soil nutrients and soil aggregates and bulk density. According to several studies, the spatial variability and depletion of mentioned soil characteristics at least are triple in the rain-fed lands which was rangelands and forest before. Moreover, wind erosion, soil salinization, intensive sediment yield and flood hazard reduce water resources and reservoir dams’ capacities. Land-use change, urbanization and over applications of chemical fertilizers and pesticides attribute to reduction in arable land and harmful agricultural crops. In addition, water crisis, hydrological lost, eutrophication event from land-use change and improper agricultural activities should not be ignored. 4-Conclusion We concluded that splash flood and dust are tangible hazards during rainfall and dry season, respectively due to land-use change and improper agricultural activates. If current land degradation and land-use change will continue, other impacts in terms of water deficit, desertification and migration can be spread throughout the semiarid region of Iran. Absolutely, overcoming these challenges depends upon saving our heritages including natural resources, unique landscapes and an attempt to do proper agricultural activities.